STRATEGI PENGEMBANGAN PERIKANAN TANGKAP TERPADU BERBASIS SUMBERDAYA UNGGULAN LOKAL: STUDI KASUS PERIKANAN CUMI DI KABUPATEN BANGKA SELATAN - Mustaruddin; Mulyono S Baskoro (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2019)
Squid resources are the fisheries potention has important economic value in South Bangka Regency. Demand for this commodity in both fresh and processed forms is estimated to continue to increase in the future. This study aims to analyze the contribution of squid fisheries, analyze their development bases, and formulate development strategies in South Bangka Regency. This study used descriptive method, LQ analysis, and AHP method. During the period of 2009-2016, the production of squid fisheries in South Bangka Regency averaged 4187.87 tons with a contribution value of Rp87,736,058,000.00 annually. This squid production follows a polynomial pattern y = -192.1x2 + 1624.x + 1745 (R² = 0.289). The base area for squid fisheries development uses: (1) liftnet is Tukak Sadai District, Lepar Pogok District, and Toboali District, (2) boat liftnet is Pongok Islands District, and (3) squid fishing is Simpang Rimba District, Batu Betumpang District, Toboali District, and Lepar Pongok District. While the priority development strategy is the coaching of human resources for squid fisheries (priority I) and improved management of the squid fisheries business (priority II) in each base area.